A Fast Recursive Algorithm for G-STBC - Zhu, Hufei; Chen, Wen; Li, Bin; Gao, Feifei (IEEE transactions on communications, 2011)
This paper proposes a fast recursive algorithm for Group-wise Space-Time Block Code (G-STBC), which takes full advantage of the Alamouti structure in the equivalent channel matrix to reduce the computational complexity. With respect to the existing efficient algorithms for G-STBC, the proposed algorithm achieves better performance and usually requires less computational complexity.